EVALUATION OF TREATMENT DRINKING WATER TREATMENT (IPAM) INSTALLATION OF SUGIHAN PDAM TIRTA WIJAYA, CILACAP REGENCY - Akbar Maulana Grantaka; Sri Hastutiningrum; Sudarsono Sudarsono (Techno LPPM, 2022)
Water is one of the important factors in fulfilling human needs. The existence of water on earth is very abundant but the quality doesn't meet the standards. The system value of a DWTP can be seen from 3 aspects, quality, quantity, and continuity of water produced. Dry season, increasing population, and the age of DWTP are things that will be faced in maintaining the three aspects of value. Seeing the several conditions experienced by PDAM Tirta Wijaya, it is necessary to conduct an evaluation to determine the performance of each unit, the quality of raw and production water, the fulfillment of water needs, the operation during the dry season and the optimization that needs to be done.  The method used is direct observation to DWTP Kesugihan. The results of the evaluation of DWTP Kesugihan are that the flocculation, sedimentation and filtration units is not comply with SNI 2774-2008, the water demand in 2029 is 1170.7 L/second.  From this study it can be concluded that the performance of the DWTP unit is categorized as quite good, the quality of raw water is still worthy of consideration, the quality of production water has met the quality standards, DWTP Kesugihan has not been able to fulfill water needs in 2029 as much as 80% coverage, there is no operational standard during the dry season. Optimization of DWTP Kesugihan by increasing the height of the filtration unit to 6.5 m, the nozzle diameter to 0.05 m and the number of nozzles to 500 and making SOPs for the dry season